Analisis Model Altman Modifikasi dan Model Springate dalam Memprediksi Kondisi Delisting pada Perusahaan yang Terdaftar di Bursa Efek Indonesia (BEI) - Ananto, Rangga Putra (Jurnal Kajian Manajemen Bisnis, 2015)
This study aims to determine empirically the financial distress prediction model on delisting companies in Indonesia Stock Exchange (IDX). Financial model used is Altman Modification and Springate. Object of study is the entire company delisting on the Stock Exchange in 2011, while the study period is 2003-2010. For comparison, also taken five of the listed companies are still the same industry sector. The method of analysis used in this study is a quantitative method. Research results show that the model Springate provide an earlier warning than Modfikasi Altman model. This is evidenced by the results of studies showing that the more capable Springate models in predicting the condition of delisting. In other words, the model is more pessimistic or conservative Springate than Altman model modification.